A lithium ion battery composite diaphragm and preparation method thereof, and a lithium ion battery
By forming a stable lithium powder lithium supplement layer on the composite separator of the lithium-ion battery, the problem of excessive lithium ion consumption during the first charging and discharging of lithium-ion batteries is solved, and higher charging and discharging efficiency and cycling performance are achieved. .
Patent Information
- Application Number
- CN202111116617.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-23
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-09-23
AI Technical Summary
During the first charging and discharging of the SEI film, lithium ion consumption is excessive due to the formation and rupture of the SEI film, which reduces the battery capacity and cycling performance.
A composite separator design is adopted, in which a lithium supplement layer is formed on the surface of the base film, and the lithium supplement layer is composed of stabilized lithium powder, including a lithium-containing metal, an inorganic lithium salt layer and a thermoplastic resin layer. This design enhances the adhesion between the diaphragm and the electrode sheet through the hot pressing process, and improves the lithium ion migration efficiency.
It improves the first charge and discharge efficiency and cycling performance of lithium-ion batteries, reduces the consumption of lithium ions during the SEI film formation and repair process, and extends the service life of the battery.
Smart Images

Figure BDA0003275562370000101 
Figure BDA0003275562370000111 
Figure BDA0003275562370000112
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion batteries, and specifically relates to a lithium-ion battery composite diaphragm and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] As a new energy source, lithium-ion batteries are favored by people for their advantages such as high specific capacity, high operating voltage, long service life, and no memory effect. With the progress of society, the requirements for the energy density of lithium-ion batteries are getting higher and higher. Usually, the negative electrode material of lithium-ion batteries will consume some lithium ions during the first charge and discharge process to form a solid electrolyte interface film covering the surface of the negative electrode material of the electrode, referred to as SEI film. The formation of SEI film consumes some lithium, which will cause the loss of lithium in the positive electrode material, thereby reducing the battery capacity and causing the first charge and discharge efficiency of the battery to be low. In addition, during the cycle of lithium-ion batteries, the SEI film will break due to the volume effect of the negative electrode material during the charge and discharge process. Therefore, during the cycle process, lithium-ion batteries will still consume additional lithium ions to repair the broken SEI film. There will be irreversible lithium in the positive and negative electrodes to varying degrees, resulting in capacity loss, which will cause serious attenuation of the battery's cycle performance. In order to improve the first charge and discharge efficiency of lithium-ion batteries and reduce the consumption of lithium by the formation of SEI film, the technology of lithium supplementation for lithium-ion batteries needs to be developed urgently.
[0003] A Chinese patent for a double-layer composite diaphragm battery and a lithium replenishment method thereof discloses a double-layer diaphragm design, adding an active lithium layer between the two diaphragms, the active lithium layer is lithium metal or an alloy or mixture of lithium and one or more of aluminum, silicon, germanium, tin and carbon, so as to achieve lithium replenishment through this design, but the safety risk of metallic lithium or lithium alloy is high. A Chinese patent for a preparation method for a lithium replenishment composite diaphragm discloses coating a glue layer on the positive electrode side of the base film and coating a lithium replenishment slurry rich in inorganic lithium salts on the negative electrode side, the lithium source is conventional various inorganic lithium salts, such as lithium carbonate, lithium hydroxide, lithium chloride, etc., but the oxidation potential of these lithium salts is usually higher than the decomposition potential of the electrolyte, and without the use of special catalysts, active lithium ions cannot be released at all. Summary of the invention
[0004] In view of the problems of low first discharge efficiency and low cycle performance of existing lithium-ion batteries, the present application provides a lithium-ion battery composite diaphragm and a lithium-ion battery thereof.
[0005] The technical solutions adopted by this application to solve the above technical problems are as follows:
[0006] On the one hand, the present application provides a lithium-ion battery composite separator, comprising a base film and a lithium replenishing layer, wherein the lithium replenishing layer is formed on at least a portion of the surface of the base film, the lithium replenishing layer comprises stabilized lithium powder, and the stabilized lithium powder comprises lithium-containing metal, an inorganic lithium salt layer and a thermoplastic resin layer, the inorganic lithium salt layer covers the outside of the lithium-containing metal, and the thermoplastic resin layer covers the outside of the inorganic lithium salt layer.
[0007] Preferably, the lithium-containing metal includes lithium or a lithium alloy, and the lithium alloy is selected from an alloy consisting of lithium and at least one metal selected from Si, Mg, Al, Sn, Be, and Ti. Preferably, the inorganic lithium salt layer includes one or more selected from lithium carbonate, lithium chloride, lithium phosphate, lithium borate, and lithium sulfate.
[0008] Preferably, the thermoplastic resin layer is selected from acrylic acid-modified polyethylene wax.
[0009] Preferably, the mass ratio of the lithium-containing metal, the inorganic salt lithium layer and the thermoplastic resin layer is 1:0.1-3:0.5-3.
[0010] Preferably, the lithium supplement layer comprises the following components by weight: 1-50 parts of a first main material, 0.1-10 parts of a first dispersant, 0.1-25 parts of stabilized lithium powder and 0.1-10 parts of a first binder.
[0011] Preferably, the lithium supplement layer comprises the following components by weight: 5-30 parts of a first main material, 0.3-8 parts of a first dispersant, 10-20 parts of stabilized lithium powder and 1-8 parts of a first binder.
[0012] Preferably, the first main material includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, and a copolymer of vinylidene fluoride and hexafluoropropylene;
[0013] The first dispersant includes one or more of polyacrylates, polyurethanes, and phosphates;
[0014] The first binder includes one or more of polyacrylates, polyolefin acrylates, polyacrylic acids, and modified acrylate copolymers.
[0015] Preferably, a glue coating layer is further included, and the glue coating layer and the lithium replenishing layer are respectively arranged on two sides of the base film.
[0016] Preferably, the thickness of the coating layer is 0.1-5 μm; the thickness of the lithium supplement layer is 0.1-5 μm; and the thickness of the base film is 5-20 μm.
[0017] Preferably, the thickness of the coating layer is 0.5-5 μm; the thickness of the lithium supplement layer is 0.5-5 μm; and the thickness of the base film is 5-16 μm.
[0018] Preferably, the coating layer comprises the following components by weight: 1-50 parts of the second main material, 0.1-10 parts of the second dispersant, 0.1-5 parts of the wetting agent and 1-10 parts of the second binder.
[0019] Preferably, the coating layer comprises the following components by weight: 5-30 parts of the second main material, 0.3-8 parts of the second dispersant, 0.1-1 parts of the wetting agent and 1-8 parts of the second binder.
[0020] Preferably, the second main material includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, and a copolymer of vinylidene fluoride and hexafluoropropylene;
[0021] The second dispersant includes one or more of polyacrylates, polyurethanes, and phosphates;
[0022] The wetting agent includes one or more of polyether silicone copolymer and nonionic lauryl alcohol polyether;
[0023] The second binder includes one or more of polyacrylates, polyolefin acrylates, polyacrylic acids, and modified acrylate copolymers.
[0024] Preferably, the base film comprises one of a polyethylene base film, a polypropylene base film, and a polypropylene / polyethylene / polypropylene composite base film.
[0025] On the other hand, the present application provides a lithium ion battery, comprising a positive electrode, a negative electrode and a separator, wherein the separator is obtained by hot pressing the above-mentioned lithium ion battery composite separator, and the temperature of the hot pressing operation is 70°C to 105°C.
[0026] Preferably, when the lithium-ion battery composite separator further includes a coating layer, the coating layer is arranged on the side of the base film facing the positive electrode, and the lithium replenishing layer is arranged on the side of the base film facing the negative electrode.
[0027] On the other hand, the present application provides a method for preparing a lithium ion battery composite diaphragm, comprising the following steps:
[0028] Preparing lithium replenishing layer slurry: dispersing stabilized lithium powder into a solvent to obtain lithium replenishing layer slurry;
[0029] The lithium replenishing layer slurry is coated onto the surface of the base film, and the solvent is removed by drying to form a lithium replenishing layer.
[0030] Preferably, the preparation of the lithium replenishing layer slurry includes the following operations: adding a first main material with a solid content of 1wt%-50wt% to a solvent, adding a first dispersant with a solid content of 0.1wt%-10wt%, and then adding stabilized lithium powder with a solid content of 0.1wt%-25wt% and a first binder with a solid content of 1wt%-10wt% by sand milling or ultrasonic dispersion, and stirring thoroughly.
[0031] Preferably, the method further comprises the following operations: preparing a coating slurry: adding a second main material having a solid content of 1wt%-50wt% to a solvent, and adding a second dispersant having a solid content of 0.1wt%-10wt% and a wetting agent having a solid content of 0.1wt%-5wt%, and then dispersing the mixture by sand milling or ultrasonic, adding a second binder having a solid content of 1wt%-10wt%, and stirring the mixture thoroughly;
[0032] Applying the adhesive layer slurry to the surface of the base film, drying to remove the solvent, and forming an adhesive layer;
[0033] The lithium replenishing layer slurry is coated on the other side of the base film, and dried to remove the solvent to form a lithium replenishing layer.
[0034] Preferably, the solvent is water.
[0035] Beneficial effects of this application:
[0036] The present application provides a composite diaphragm for lithium-ion batteries, wherein a lithium replenishing layer is formed on at least part of the surface of a base film, and the lithium replenishing layer includes stabilized lithium powder, wherein the stabilized lithium powder includes lithium-containing metal, an inorganic lithium salt layer and a thermoplastic resin layer, wherein the inorganic lithium salt layer covers the outside of the lithium-containing metal, and the thermoplastic resin layer covers the outside of the inorganic lithium salt layer. The thermoplastic resin layer has adhesive properties, melts during the hot pressing process, and can enhance the adhesive force between the diaphragm and the negative electrode sheet. The lithium-containing metal can replenish the lithium ions consumed by the formation of a solid electrolyte membrane (SEI membrane) by the negative electrode material during the first charge and discharge process of the battery, thereby improving the first charge and discharge efficiency of the battery; at the same time, it replenishes the lithium ions consumed by the repair of the ruptured solid electrolyte membrane (SEI membrane) during the cycle of the lithium-ion battery, thereby improving the cycle performance of the battery. The structure of the stabilized lithium powder has good stability, and can stably exist in air, NMP, and environments containing water. DETAILED DESCRIPTION
[0037] In order to make the technical problems, technical solutions and beneficial effects solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0038] On the one hand, the present application provides a lithium-ion battery composite separator, comprising a base film and a lithium replenishing layer, wherein the lithium replenishing layer is formed on at least a portion of the surface of the base film, the lithium replenishing layer comprises stabilized lithium powder, and the stabilized lithium powder comprises lithium-containing metal, an inorganic lithium salt layer and a thermoplastic resin layer, the inorganic lithium salt layer covers the outside of the lithium-containing metal, and the thermoplastic resin layer covers the outside of the inorganic lithium salt layer.
[0039] In some embodiments, the stabilized lithium powder provided by the present application is different from the double-layer core-shell structure of conventional inert lithium powder in that the stabilized lithium powder used in the present application can exist stably in air, NMP and water without any reaction, and the stabilized lithium powder has good stability; although conventional inert lithium powder is inactive, it still needs to be used in a non-aqueous solvent, and it is inconvenient to use inert lithium powder to prepare lithium-replenishing slurry or to use the slurry prepared by inert lithium powder for coating to prepare lithium-replenishing composite diaphragm. The present application applies stabilized lithium powder to the diaphragm, forms a lithium supplement layer on at least part of the surface of the base film, and the thermoplastic resin layer in the stabilized lithium powder has adhesive properties. After the hot pressing process, the thermoplastic resin melts, which can enhance the adhesive force between the diaphragm and the electrode, shorten the lithium ion transmission distance, and improve the lithium ion migration efficiency; the inorganic lithium salt layer included in the stabilized lithium powder covers the outside of the lithium-containing metal, so that the metallic lithium can exist stably in the environment of air, water or NMP; the lithium-containing metal supplements the lithium ions consumed by the solid electrolyte membrane (SEI membrane) formed on the surface of the negative electrode material during the first charge and discharge process of the battery, reduces the consumption of lithium in the active material of the positive electrode sheet, increases the discharge capacity, and thus improves the first charge and discharge efficiency of the battery; the lithium-containing metal can also supplement the lithium ions consumed by the repair of the ruptured SEI membrane during the cycle of the lithium-ion battery, reduces the consumption of lithium in the active material of the positive electrode sheet, and improves the battery cycle performance.
[0040] The lithium-containing metal includes lithium element or lithium alloy, and the lithium alloy is selected from an alloy composed of at least one metal selected from Si, Mg, Al, Sn, Be, and Ti and lithium. In some embodiments, the present application does not limit the type of metal selected above to form an alloy with lithium, but the selection of non-lithium metal types in the lithium alloy requires that when the battery is charged, the lithium in the lithium alloy should release lithium ions first, and form a solid electrolyte membrane (SEI membrane) on the surface of the negative electrode material to supplement the extra consumed lithium ions. At the same time, the non-lithium metal in the lithium alloy shall not cause an increase in the side reactions of the lithium ion battery, affecting the electrical performance of the lithium ion battery. The inorganic lithium salt layer includes one or more of lithium carbonate, lithium chloride, lithium phosphate, lithium borate, and lithium sulfate. In some embodiments, the present application does not limit the type of inorganic lithium salt layer, as long as the lithium-containing metal that can be coated can stably exist in water, NMP or air, and the ions in the inorganic lithium salt do not cause an increase in the side reactions of the lithium ion battery, affecting the electrical performance of the lithium ion battery.
[0041] The thermoplastic resin layer is selected from acrylic acid modified polyethylene wax. Acrylic acid modified polyethylene wax has strong adhesion and melts at around 90°C, which is compatible with the temperature range of the hot pressing process; after the hot pressing process, the acrylic acid modified polyethylene wax enhances the adhesion between the diaphragm and the pole piece, shortens the lithium ion transmission distance, improves the lithium ion migration efficiency, reduces the internal resistance of the battery, and improves the battery electrical performance. For lithium-ion batteries, acrylic acid modified polyethylene wax does not introduce new impurities and does not increase the side reactions of lithium-ion batteries. The present application does not limit the type of thermoplastic resin, which may be polyethylene wax, or other types of thermoplastic resins that have adhesion, melt at around 90°C, and do not increase the side reactions of lithium-ion batteries.
[0042] A person skilled in the art who knows the structure of the stabilized lithium powder can know the preparation method of the stabilized lithium powder according to the common knowledge in the field of chemical synthesis. As an example of this application:
[0043] The thermoplastic resin layer can be formed on the surface by in-situ polymerization of a lithium-containing metal coated with an inorganic lithium salt layer.
[0044] The mass ratio of lithium metal, inorganic salt lithium layer and thermoplastic resin layer in the stabilized lithium powder is: 1: 0.1 ~ 3: 0.5 ~ 3
[0045] In some embodiments, the mass ratio of lithium metal, inorganic salt lithium layer and thermoplastic resin layer in the stabilized lithium powder is lower than the above range value, the adhesion between the diaphragm and the electrode is reduced, the content of lithium ions that can participate in the lithium replenishment reaction is reduced, the transmission distance of lithium ions is increased, the migration efficiency of lithium ions is reduced, and the battery cycle performance is reduced; if it is higher than the above range value, the overall weight of the battery increases and the energy density of the battery is reduced.
[0046] The lithium supplement layer comprises the following components by weight: 1-50 parts of a first main material, 0.1-10 parts of a first dispersant, 0.1-25 parts of stabilized lithium powder and 0.1-10 parts of a first binder.
[0047] Furthermore, the lithium supplement layer includes the following components by weight: 5-30 parts of the first main material, 0.3-8 parts of the first dispersant, 10-20 parts of stabilized lithium powder and 1-8 parts of the first binder.
[0048] The first main material includes one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyhexafluoropropylene (PHFP), and copolymers of vinylidene fluoride and hexafluoropropylene; the first dispersant includes one or more of polyacrylates, polyurethanes, and phosphates; the first binder includes one or more of polyacrylates, polyolefin acrylates, polyacrylic acids, and modified acrylate copolymers.
[0049] In some embodiments, the weight component of the stabilized lithium powder in the lithium replenishing layer is 0.1-25 parts, preferably 10-20 parts, the first dispersant is 0.3-8 parts, the first main material is preferably 5-30 parts, and the first binder is preferably 1-8 parts; by making each weight component in the lithium replenishing layer within a suitable range, the prepared lithium ion battery has a higher first charge and discharge efficiency and better cycle performance. The stabilized lithium powder containing the thermoplastic resin layer is more conducive to being dispersed in the first main material and combined with the first binder, forming a more stable lithium replenishing slurry under the action of the dispersant, and forming a lithium replenishing layer with a uniform distribution of the stabilized lithium powder after coating, thereby improving the battery electrical performance.
[0050] The lithium-ion battery composite separator provided in the present application also includes a glue coating layer, and the glue coating layer and the lithium supplement layer are respectively arranged on two sides of the base film.
[0051] In some embodiments, a rubber coating layer is provided on one side of the diaphragm, and a lithium replenishing layer is provided on the other side. The rubber coating layer can increase the adhesion between the diaphragm and the electrode. The lithium replenishing layer also contains adhesive substances, which also increase the adhesion between the diaphragm and the electrode, ensuring the consistency of the distance between the two sides of the diaphragm and the corresponding electrode, thereby ensuring the consistency of the lithium ion transmission distance on both sides of the lithium ion diaphragm.
[0052] In some embodiments, the thickness of the coating layer is 0.1-5 μm, the thickness of the lithium supplement layer is 0.1-5 μm, and the thickness of the base film is 5-20 μm. Preferably, the thickness of the coating layer is 0.5-5 μm, the thickness of the lithium supplement layer is 0.5-5 μm, and the thickness of the base film is 5-16 μm.
[0053] In some embodiments, the battery cells prepared by the preferred coating layer thickness, lithium supplement layer thickness, and base film thickness have good battery hardness after the hot pressing process, which is convenient for battery cell transportation and improves production efficiency; and the first charge and discharge efficiency of the prepared lithium-ion battery is improved, while the battery cycle performance is improved and the battery electrical performance is improved. In some embodiments, the thickness of the coating layer and the lithium supplement layer are both 0.1-5μm. If the thickness is higher than 5μm, the volume of a single battery cell increases, and it is difficult to put the battery into the shell, and the volume energy density of the battery decreases; if the thickness is lower than 0.1μm, it is difficult to form a coating layer and a lithium supplement layer, and the charge and discharge efficiency and cycle performance of the prepared battery are not significantly improved.
[0054] The coating layer comprises the following components by weight: 1-50 parts of the second main material, 0.1-10 parts of the second dispersant, 0.1-5 parts of the wetting agent and 1-10 parts of the second binder.
[0055] The coating layer comprises the following components by weight: 5-30 parts of the second main material, 0.3-8 parts of the second dispersant, 0.1-1 parts of the wetting agent and 1-8 parts of the second binder.
[0056] The second main material includes one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyhexafluoropropylene (PHFP), and a copolymer of vinylidene fluoride and hexafluoropropylene;
[0057] The second dispersant includes one or more of polyacrylates, polyurethanes, and phosphates;
[0058] The wetting agent includes one or more of polyether silicone copolymer and nonionic lauryl alcohol polyether;
[0059] The binder includes one or more of polyacrylates, polyolefin acrylates, polyacrylic acids, and modified acrylate copolymers.
[0060] In some embodiments, the weight component of the second main material in the coating layer is preferably 5-30 parts, the second dispersant is preferably 0.3-8 parts, the second binder is preferably 1-8 parts, and the wetting agent is preferably 0.1-1 parts; by making the weight components of each component in the coating layer within a suitable range, the diaphragm prepared by the coating layer coated on the surface of the base film has good adhesion to the positive electrode, shortening the transmission distance of lithium ions, reducing the internal resistance of the battery, and improving the battery cycle performance.
[0061] In some embodiments, the second main ingredient of the coating layer is of the same type and weight composition as the first main ingredient in the lithium replenishing layer, and the type and weight composition of the binder are also the same. In this way, the coating layer and the lithium replenishing layer on both sides of the base film contain the same type of binder. After the battery cell made of the prepared diaphragm is subjected to a hot pressing process, the bonding force between the diaphragm and the positive electrode sheet or the diaphragm and the negative electrode sheet is basically the same, the distance between the diaphragm and the positive electrode sheet, and the distance between the diaphragm and the negative electrode sheet are similar, the transmission distance of the lithium-ion battery is basically the same, and the consistency of the battery capacity and cycle performance can be improved.
[0062] In some embodiments, the present application does not limit the types of the first main material, the second main material, the first dispersant, the second dispersant, the first binder, and the second binder; the main functions of the first main material, the second main material, the first binder, and the second binder are to enhance the bonding force between the diaphragm and the pole piece. The first main material also has the function of bonding and evenly dispersing the stabilized lithium powder into the solvent. The coating layer contains a wetting agent, which reduces the surface tension or interfacial tension of the second main material, etc., so that the solvent water can wet the second main material and other materials; at the same time, the wetting agent reduces the interfacial tension of the fixed surface, which is more conducive to the slurry coating and the base film surface.
[0063] The base film includes one of a polyethylene base film, a polypropylene base film, and a polypropylene / polyethylene / polypropylene composite base film.
[0064] On the other hand, the present application provides a method for preparing a lithium ion battery composite diaphragm, comprising the following steps:
[0065] Preparation of glue coating slurry:
[0066] Add the second main material with a solid content of 1wt%-50wt% into the solvent, and add the second dispersant with a solid content of 0.1wt%-10wt% and the wetting agent with a solid content of 0.1wt%-5wt%, then disperse by sand milling or ultrasonication for 1-4h, add the second binder with a solid content of 1wt%-10wt%, and stir thoroughly for 0.5-1h;
[0067] Preparation of lithium supplementation layer slurry:
[0068] Add a first main material with a solid content of 1wt%-50wt% to a solvent, add a first dispersant with a solid content of 0.1wt%-10wt%, then disperse by sand milling or ultrasonication for 1-4h, add stabilized lithium powder with a solid content of 0.1wt%-25wt% and a first binder with a solid content of 1wt%-10wt%, and stir thoroughly for 0.5-1h;
[0069] Preparation of lithium-ion battery composite separator:
[0070] The adhesive layer slurry is applied to one side of the base film and dried at 30°C-80°C to form a adhesive layer; then the lithium replenishing layer slurry is applied to the other side of the base film and dried at 30°C-80°C to form a lithium replenishing layer.
[0071] In the preparation of lithium supplement layer slurry and glue coating layer slurry, the solvent is water.
[0072] The thickness of the glue coating layer is 0.1-5 μm; the thickness of the lithium supplement layer is 0.1-5 μm; and the thickness of the base film is 5-20 μm.
[0073] In some embodiments, the lithium replenishment layer slurry prepared in the present application has a stabilized lithium powder solid content of 0.1wt%-25wt%, the stabilized lithium powder solid content is lower than the range value, the inner shell metal lithium content is relatively small, and it cannot meet the consumption of lithium ions in the formation of SEI film during the first charge and discharge of the lithium-ion battery, or it cannot meet the consumption of lithium ions in repairing the broken SEI film during the cycle of the lithium-ion battery; the stabilized lithium powder solid content is higher than the range value, the corresponding main material solid content is reduced, the bonding force between the diaphragm and the electrode is reduced, the lithium ion migration rate is reduced, the battery cycle performance is reduced, and the life is reduced.
[0074] In some embodiments, the present application provides a method for preparing a lithium-ion battery composite diaphragm, in which the solid content of the second main material in the preparation of the coating layer slurry is preferably 5wt%-30wt%, the solid content of the second dispersant is preferably 0.3wt%-8wt%, the solid content of the wetting agent is preferably 0.1wt%-1wt%, and the solid content of the second binder is preferably 1wt%-8wt%.
[0075] In some embodiments, the present application provides a method for preparing a lithium-ion battery composite membrane. In the preparation of the lithium replenishing layer slurry, the solid content of the first main material is preferably 5wt%-30wt%, the solid content of the first dispersant is preferably 0.3wt%-8wt%, the solid content of the second binder is preferably 1wt%-8wt%, and the solid content of the stabilized lithium powder is preferably 10wt%-20wt%.
[0076] The present application provides a method for preparing a lithium-ion battery composite separator, wherein the thickness of the coating layer is preferably 0.5-5 μm; the thickness of the lithium supplement layer is preferably 0.5-5 μm; and the thickness of the base film is preferably 5-16 μm.
[0077] In some embodiments, the present application provides preferred types and solid content parameters of the first main material, the second main material, the dispersant, the binder, the wetting agent, and the stabilized lithium powder in the preparation of the coating layer slurry and the lithium replenishing layer slurry, as well as the preferred thicknesses of the coating layer, the lithium replenishing layer, and the base film, and the prepared lithium-ion battery composite membrane has better performance.
[0078] On the other hand, the present application provides a lithium-ion battery, comprising a positive electrode, a negative electrode, and a diaphragm prepared by hot pressing a lithium-ion battery composite diaphragm.
[0079] In some embodiments, a lithium-ion battery prepared by assembling a separator prepared by hot pressing a lithium-ion battery composite separator with a positive electrode sheet, a negative electrode sheet, etc. can improve the battery's initial charge and discharge efficiency and battery cycle performance.
[0080] The lithium-ion battery composite diaphragm also includes a glue coating layer, which is arranged on the side of the base film facing the positive electrode, and the lithium supplement layer is arranged on the side of the base film facing the negative electrode. The temperature of the hot pressing operation is 70°C to 105°C.
[0081] In some embodiments, the present application adds a lithium supplement layer on the negative electrode side of the diaphragm, and the stabilized lithium powder can supplement the lithium ions consumed by the negative electrode material during the first charge and discharge process of the battery due to the generation of the SEI film, thereby improving the first charge and discharge efficiency of the battery. In addition, during the cycle of the battery, the SEI film will break due to the volume effect of the negative electrode material during the charge and discharge process. Therefore, during the cycle, the lithium-ion battery will still consume additional lithium ions to repair the broken SEI film, and the lithium supplement layer can also supplement it, thereby improving the cycle performance of the battery. The present application adds a glue layer on the positive electrode side of the diaphragm to ensure that the diaphragm can have a greater bonding force with the positive electrode sheet after hot pressing, which can improve the hardness of the battery cell and make it less likely to deform. At the same time, the lithium supplement layer formed on the other side of the diaphragm is facing the negative electrode sheet, and the diaphragm also has a certain bonding force with the negative electrode sheet. After the hot pressing process between the positive and negative electrode sheets and the diaphragm, the bonding force increases, and at the same time, the distance between the positive and negative electrode sheets is shortened, and the lithium ion transmission distance is shortened, which improves the lithium ion migration efficiency and improves the cycle performance of the lithium ion battery.
[0082] In some embodiments, a lithium-ion battery composite diaphragm is obtained by hot pressing, wherein the temperature of the hot pressing operation is 70°C to 105°C; below this temperature range, the bonding force between the glue layer, the lithium supplement layer and the base film is weak, and the glue layer and the lithium supplement layer are easy to fall off during the preparation of the battery cell; above this temperature range, the closed-pore temperature of the diaphragm is exceeded, and the lithium-ion battery is not easy to pass through the diaphragm pores, resulting in reduced battery capacity, increased internal resistance, and reduced cycle efficiency.
[0083] Preparation method of positive electrode sheet: The active material NCM811, acetylene black and polyvinylidene fluoride (purchased from Dongguan Qingfeng Plastic Raw Materials Co., Ltd., with a brand name of FR900) are dissolved in N-methylpyrrolidone at a weight ratio of 90:5:5 to form a positive electrode slurry with a solid content of 50wt%, and the positive electrode slurry obtained after uniform stirring is coated on both sides of an aluminum foil with a thickness of 16μm, and baked at 110℃±5℃, and then calendered and vacuum dried to form a material layer with a thickness of 140μm±5μm to obtain a positive electrode sheet.
[0084] Negative electrode sheet preparation method: Asphalt-coated natural graphite (asphalt coating amount is 2wt%) and conductive carbon black, styrene-butadiene rubber, and carboxymethyl cellulose are dispersed in deionized water in a weight ratio of 95:1:1.7:2.3 to obtain a negative electrode slurry, and the evenly stirred negative electrode slurry is coated on both sides of a copper foil with a thickness of 10μm, and baked at 110℃±5℃, and then calendered and vacuum dried to form a material layer with a thickness of 100μm±5μm to obtain a negative electrode material.
[0085] Electrolyte: ED:DMC:EMC:DEC=1:1:1:1, LiPF6 concentration is 1 mol / L.
[0086] Preparation of battery: The positive and negative electrodes and the experimentally prepared separator are wound into a square lithium-ion battery pack, in which the glue coating layer faces the positive electrode and the lithium supplement layer faces the negative electrode. After hot pressing, they are loaded into a battery shell and welded. Subsequently, the electrolyte is injected into the battery shell and sealed to make a 453450A lithium-ion battery.
[0087] The present application is further described in detail below through several examples. The base films used in the following experiments are all 12μm polyethylene base films (from the same batch), and the stabilized lithium powder used has a three-layer core-shell structure with a lithium metal core, a lithium carbonate middle layer, and an acrylic acid-modified polyethylene wax outer shell.
[0088] Example 1
[0089] (1) Preparation of glue coating slurry:
[0090] Add polyvinylidene fluoride (PVDF) with a solid content of 20wt% as the main material of the adhesive layer to the solvent deionized water, add polyacrylate with a solid content of 2.0wt% as the dispersant and polyether silicone copolymer with a solid content of 0.5wt% as the wetting agent, and then disperse by ultrasound for 3h, add polyacrylate with a solid content of 5.0wt% as the binder, and stir thoroughly for 0.8h;
[0091] (2) Preparation of lithium supplementation layer slurry:
[0092] Add 20wt% of the main material polyvinylidene fluoride (PVDF) to the solvent, add 2.0wt% of the dispersant polyacrylate, then disperse by ultrasound for 3h, add 15% of the solid content of stabilized lithium powder and 5.0wt% of the solid content of binder polyacrylate, and stir thoroughly for 0.8h;
[0093] (3) Applying the coating layer slurry to one side of the base film to form a coating layer, and drying it at 80°C, and then applying the lithium replenishing layer slurry to the other side of the base film to form a lithium replenishing layer, and drying it at 80°C; the thickness of the formed coating layer is 2 μm; the thickness of the formed lithium replenishing layer is 2 μm.
[0094] The preparation method of the lithium-ion battery composite separator in Example 2-6 and the preparation method of the glue layer or the lithium supplement layer in Comparative Example 1-2 are the same as in Example 1; the dispersion parameters, stirring parameters, and baking parameters in the slurry preparation process in Example 2-6 and Comparative Example 1-2 are shown in Table 1; the types of materials such as binders and dispersants, solid contents, and the thicknesses of the glue layer and the lithium supplement layer in Example 2-6 and Comparative Example 1-2 are shown in Table 2.
[0095] Table 1 Dispersion parameters, stirring parameters, and baking parameters during the slurry preparation process of Example 2-5 are as follows
[0096]
[0097] Table 2 Parameters of different material types, solid contents and coating thicknesses in the examples and comparative examples are as follows
[0098]
[0099]
[0100] According to the above-mentioned method for preparing lithium-ion batteries, lithium-ion batteries were prepared using the separators prepared in Examples 1-6 and Comparative Examples 1-2. After standing for 24 hours, the first charge efficiency test and the cycle performance test were performed.
[0101] Room temperature cycle performance: The battery was loaded into the battery performance tester BS-9300, and 500 cycles were performed at room temperature of 25°C with a current of 1C, an upper voltage of 4.2V, and a lower voltage of 2.5V. The ratio of the 500th discharge capacity to the 1st discharge capacity is the room temperature cycle capacity retention rate of the battery for 500 times. The test results are shown in Table 3.
[0102] Table 3 Cycle data of lithium ion batteries prepared in Examples 1-5 and Comparative Examples 1-3
[0103]
[0104]
[0105] As can be seen from Table 3, the first charge and discharge efficiency of Examples 1-5 is significantly higher than that of Comparative Examples 1 and 2, indicating that after hot pressing, the lithium replenishing layer replenishes the lithium ions consumed extra inside the battery to form the SEI film during the first charge and discharge process. In Example 6, due to the presence of a lithium replenishing layer, its first charge and discharge efficiency is higher than that of Comparative Examples 1 and 2. Example 6 has a lithium replenishing layer and no glue coating layer, and the first charge and discharge efficiency of the battery is much higher than that of Comparative Example 2, indicating that the lithium replenishing effect of the lithium replenishing layer is better, and the lithium ions forming the SEI film are effectively replenished. The 500 times room temperature capacity retention rate of Examples 1-5 is significantly improved compared with Comparative Example 1. This is because the glue coating layer and the lithium replenishing layer of Examples 1-5 can be effectively bonded to the positive and negative pole pieces after hot pressing, shortening the lithium ion transmission distance. At the same time, the lithium replenishing layer can replenish the additional lithium ion consumption caused by the rupture of the SEI film during the battery cycle. Therefore, compared with Comparative Example 1, Examples 1-5 have better cycle performance. Comparative Example 2 and Example 6 have a glue coating layer or a lithium supplement layer, and can be closely attached to the positive electrode sheet or the negative electrode sheet after hot pressing. Therefore, the cycle performance is also improved to a certain extent compared with Comparative Example 1.
[0106] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A lithium-ion battery composite diaphragm, characterized in that: The invention comprises a base film and a lithium replenishing layer, wherein the lithium replenishing layer is formed on at least a part of the surface of the base film, the lithium replenishing layer comprises stabilized lithium powder, the stabilized lithium powder is composed of lithium-containing metal, an inorganic lithium salt layer and a thermoplastic resin layer, the inorganic lithium salt layer covers the outside of the lithium-containing metal, and the thermoplastic resin layer covers the outside of the inorganic lithium salt layer; The mass ratio of the lithium-containing metal, the inorganic lithium salt layer and the thermoplastic resin layer is 1:0.1-3:0.5-3; The thermoplastic resin layer is selected from acrylic acid-modified polyethylene wax; The lithium supplement layer comprises the following components by weight: 5-30 parts of a first main material, 0.3-8 parts of a first dispersant, 10-20 parts of stabilized lithium powder and 1-8 parts of a first binder; The first main material is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, and a copolymer of vinylidene fluoride and hexafluoropropylene.
2. A lithium-ion battery composite separator according to claim 1, characterized in that: The lithium-containing metal includes lithium alone or a lithium alloy, and the lithium alloy is selected from an alloy consisting of lithium and at least one metal selected from Si, Mg, Al, Sn, Be, and Ti.
3. A lithium-ion battery composite separator according to claim 1, characterized in that: The inorganic lithium salt layer includes one or more of lithium carbonate, lithium chloride, lithium phosphate, lithium borate, and lithium sulfate.
4. A lithium-ion battery composite separator according to claim 1, characterized in that: The first dispersant includes one or more of polyacrylates, polyurethanes, and phosphates; The first binder includes one or more of polyacrylates, polyolefin acrylates, polyacrylic acids, and modified acrylate copolymers.
5. A lithium-ion battery composite separator according to claim 1, characterized in that: It also includes a glue coating layer, and the glue coating layer and the lithium supplement layer are respectively arranged on two sides of the base film.
6. A lithium-ion battery composite separator according to claim 5, characterized in that: The thickness of the coating layer is 0.1-5 μm; the thickness of the lithium supplement layer is 0.1-5 μm; and the thickness of the base film is 5-20 μm.
7. A lithium-ion battery composite separator according to claim 5, characterized in that: The thickness of the coating layer is 0.5-5 μm; the thickness of the lithium supplement layer is 0.5-5 μm; and the thickness of the base film is 5-16 μm.
8. A lithium-ion battery composite separator according to claim 5, characterized in that: The coating layer comprises the following components by weight: 1-50 parts of a second main material, 0.1-10 parts of a second dispersant, 0.1-5 parts of a wetting agent and 1-10 parts of a second binder.
9. A lithium-ion battery composite separator according to claim 5, characterized in that: The coating layer comprises the following components by weight: 5-30 parts of a second main material, 0.3-8 parts of a second dispersant, 0.1-1 parts of a wetting agent and 1-8 parts of a second binder.
10. A lithium ion battery composite separator according to claim 8 or 9, characterized in that: The second main material includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, and a copolymer of vinylidene fluoride and hexafluoropropylene; The second dispersant includes one or more of polyacrylates, polyurethanes, and phosphates; The wetting agent includes one or more of polyether silicone copolymer and nonionic lauryl alcohol polyether; The second binder includes one or more of polyacrylates, polyolefin acrylates, polyacrylic acids, and modified acrylate copolymers.
11. A lithium-ion battery composite separator according to claim 1, characterized in that: The base film includes one of a polyethylene base film, a polypropylene base film, and a polypropylene / polyethylene / polypropylene composite base film.
12. A lithium ion battery comprising a positive electrode, a negative electrode and a separator, wherein the separator is obtained by hot pressing the lithium ion battery composite separator according to any one of claims 1 to 11, and the temperature of the hot pressing operation is 70°C-105°C.
13. A lithium ion battery according to claim 12, characterized in that: When the lithium-ion battery composite separator further includes a coating layer, the coating layer is arranged on the side of the base film facing the positive electrode, and the lithium supplement layer is arranged on the side of the base film facing the negative electrode.
14. A method for preparing a composite separator for a lithium ion battery according to any one of claims 1 to 11, characterized in that: The steps include: Preparing lithium replenishing layer slurry: dispersing stabilized lithium powder into a solvent to obtain lithium replenishing layer slurry; The lithium replenishing layer slurry is coated onto the surface of the base film, and the solvent is removed by drying to form a lithium replenishing layer.
15. The method for preparing a lithium ion battery composite diaphragm according to claim 14, characterized in that: The preparation of the lithium replenishing layer slurry includes the following operations: adding a first main material with a solid content of 1wt%-50wt% into a solvent, adding a first dispersant with a solid content of 0.1wt%-10wt%, then dispersing by sand milling or ultrasonic grinding, adding stabilized lithium powder with a solid content of 0.1wt%-25wt% and a first binder with a solid content of 1wt%-10wt%, and stirring thoroughly.
16. The method for preparing a composite separator for a lithium-ion battery according to claim 14, characterized in that: The process also includes the following steps: preparing a coating layer slurry: adding a second main material having a solid content of 1wt%-50wt% to a solvent, adding a second dispersant having a solid content of 0.1wt%-10wt% and a wetting agent having a solid content of 0.1wt%-5wt%, and then dispersing the mixture by sand milling or ultrasonication, adding a second binder having a solid content of 1wt%-10wt%, and stirring the mixture thoroughly; Applying the adhesive layer slurry to the surface of the base film, drying to remove the solvent, and forming an adhesive layer; The lithium replenishing layer slurry is coated on the other side of the base film, and dried to remove the solvent to form a lithium replenishing layer.
17. A method for preparing a lithium ion battery composite diaphragm according to any one of claims 15 or 16, characterized in that: The solvent is water.
Citation Information
Patent Citations
Lithium ion battery, and ceramic diaphragm of lithium ion battery
CN106299214A
Method for preparing lithium-supplementing composite diaphragm
CN110571391A